An 40 Ar/ 39 Ar study of the Cape Breton Highlands, Nova Scotia: thermal histories and tectonic implications - Reynolds, P. H.; Jamieson, R. A.; Barr, S. M.; Raeside, R. P. (Canadian Journal of Earth Sciences, 1989)
Forty new 40 Ar/ 39 Ar age spectra on micas and amphiboles from both granitic and metamorphic rocks show that two geologically distinct terranes in the Cape Breton Highlands (Nova Scotia) have had contrasting thermal histories. Some plutons in the Bras d'Or Terrane in the southeastern highlands apparently cooled through the hornblende (or muscovite) closure temperature immediately following Precambrian to Cambrian intrusion. Other rock units in this terrane, particularly in the west, have been variably overprinted by a Silurian tectonothermal event, probably associated with juxtaposition of the Bras d'Or Terrane with the Aspy Terrane to the northwest. Gneisses at Kellys Mountain in the southeastern Bras d'Or Terrane apparently were not overprinted by this event.Argon data from the Aspy Terrane suggest that Silurian deposition, deformation, and metamorphism were followed by rapid cooling through hornblende and biotite closure temperatures in the Middle Devonian. This probably resulted from uplift and exhumation of the terrane as it collided with the Appalachian Orogen to the northwest. The Cheticamp Pluton in the western part of the Aspy Terrane, which does not appear to have been significantly affected by Silurian–Devonian tectonothermal events, may represent an outlier of the Bras d'Or Terrane. The Aspy Terrane records an Acadian tectonothermal history similar to that of the Gander Zone in southwestern Newfoundland.